Towards a glacial-sensitive model of island biogeography - Fernandez-Palacios, JM; Rijsdijk, KF; Norder, SJ; Otto, R; de Nascimento, L; Fernández-Lugo, S; Tjørve, E; Whittaker, RJ (Wiley, 2015)
Although the role that Pleistocene glacial cycles have played in shaping the present biota of oceanic islands world-wide has long been recognized, their geographical, biogeographical and ecological implications have not yet been fully incorporated within existing biogeographical models. Here we summarize the different types of impacts that glacial cycles may have had on oceanic islands, including cyclic changes in climate, shifts in marine currents and wind regimes and, especially, cycles of sea level change. The latter have affected geographical parameters such as island area, isolation and elevation. They have also influenced the configurations of archipelagos via island fusion and fission, and cycles of seamount emergence and submergence. We hypothesize that these sea level cycles have had significant impacts on the biogeographical processes shaping oceanic island biotas, influencing the rates and patterns of immigration and extinction and hence species richness. Here we provide a first step toward the development of a glacial-sensitive model of island biogeography, representing the tentative temporal evolution of those biogeographical parameters during the last glacial cycle. From this reasoning we attempt to derive predictions regarding the imprint of sea level cycles on genetic, demographic or biogeographical patterns within remote island biotas.